Protein ubiquitination, degradation and the proteasome in neuro-degenerative disorders: No clear evidence for a significant pathogenetic role of proteasome failure in Alzheimer disease and related disorders - Schmitt, Horst Peter (Medical hypotheses, 2006)
Summary: It has recently been proposed that Alzheimer disease (AD) might be initiated by a molecular ‘hit’ into a regulatory protein, e.g. a cell surface receptor [Schmitt HP. Neuro-modulation, aminergic neuro-disinhibition and neuro-degeneration: draft of a comprehensive theory for Alzheimer disease. Med Hypoth 2005;65:1106-19]. However, other substrates, in particular intra-cellular protein complexes such as the ubiquitin/proteasome system (UPS) could as well serve as a targets for such a ‘hit’ which might insert a mutation or induce conformational changes resulting in functional failure of protein degradation along the ubiquitin/proteasome proteolytic pathway. It has been claimed that impairment of the large multi-catalytic protease complex, the 20S/26S proteasome, might represent a key factor in the early pathogenesis of neuro-degenerative disorders characterized by the formation of abnormal protein aggregates such as neuronal cytoplasmic or nuclear inclusion bodies and fibrillary deposits. This article aims to review critically whether current information really supports the idea that impairment of the UPS might play a significant role in the early pathogenesis of neuro-degenerative disorders, with special emphasis on AD. The data provided in favour of proteasome impairment were, as a rule, revealed in in vitro experiments which cannot be unequivocally transfered to the in vivo conditions in neuro-degeneration. The author concludes that there is yet no clear evidence of a pivotal role of proteasome failure in the early pathogenesis of AD.